GAYA HIDUP PENGGUNA TELEPON SELULER BLACKBERRY - Dwi Susanti (Universitas muhammadiyah malang, 2011)
Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah MalangE-mail: dwisusanti39@yahoo.comABSTRACTThis paper explains the lifestyle of the Blackberry mobile phone users. Analysis tool used ClusterAnalysis. Its using two assumptions as the benchmark of a good cluster that is to have an internalhomogeneity (within clusters); the similarities between member in one cluster and external heterogeneity(the between clusters), i.e. the difference between a single cluster with the other clusters. Analysislifestyle Blackberry cell phone users conducted on students at Muhammadiyah University ofMalang used questionnaires. The results shows three lifestyle groups, namely fulfilled, believer andmaker groups. Based on those results, it can be used as a guidance for performing the segmentationinto marketers, especially marketers of Blackberry mobile phones.Keywords: lifestyle, cluster analysis, fulfilled, believer, maker